Contributing factors in academic performance and troubles associated with teaching in areas of physics in engineering students (2020)
Learning processes are affected by a series of factors, both individual students and the institutional environment in which they develop. The present work is developed under the context of learning processes in areas of physics in engineering students, belonging to the academic program of technology in industrial processes, considering the socio-demographic and academic variables that affect students and that in turn affect student dropout. Data collection instruments were applied to a population group of 90 students, allowing to propose strategic scenarios that would contribute to improve the quality of academic processes and students' skills in the study of mechanical and electromagnetic physics. It was determined that the role played by teachers and the methodology in which they teach their students, the physical conditions and teaching methods directly affect the effectiveness of learning and academic performance. It was also demonstrated that the lack of prior knowledge in the fundamentals of logic-mathematics and basic physics are determining aspects in the failure and repetition of the subjects.